NIS-promoted three-component reaction of 3-oxo-3-arylpropanenitriles with arylsulfonyl hydrazides. Issue 17 (13th April 2021) - Wei, Yueting; Liu, Ping; Liu, Yali; He, Jing; Li, Xuezhen; Li, Shiwu; Zhao, Jixing
Abstract : An expanded inventory of 3-aryl-4-(arylthio)-1 H -pyrazol-5-amines were synthesized by a new three-component reaction of 3-oxo-3-arylpropanenitriles with arylsulfonyl hydrazides under the action of NIS. Abstract : A new three-component reaction of 3-oxo-3-arylpropanenitriles with arylsulfonyl hydrazides has been established, and an expanded inventory of 3-aryl-4-(arylthio)-1 H -pyrazol-5-amines is synthesized by sequential cyclization and sulfenylation reactions under the action of NIS. In addition to the attractive features of multicomponent reactions, the protocol presents broad substrate scope, good functional group tolerance and mild reaction conditions. The utility of this procedure is further established by gram-scale synthesis as well as the diversified transformations of the products to useful compounds.